Current Status of Indian Trichogramma Spp. along with their Distributional Record and Host Range - Yousuf, Mohd.; Ikram, Mohsin; Faisal, Mohd. (Indian Forester, 2015)
Egg parasitoids belonging to the genus Trichogramma are well known biological control agents, being utilised in applied biological control of insect pests, particularly against lepidopterous pests of agricultural crops and forest tree species. In the present paper, important diagnostic characters of all Indian species of Trichogramma have been given, in brief. Host-range of the Indian Trichogramma spp., along with their distributional record has also been up-dated. Scope of application of Trichogramma spp. for controlling the key insect pests has also been discussed.